PETANDA BIOLOGIK TERKINI LUPUS NEFRITIS - Hani Susianti; Kusworini Handono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2014)
Lupus Nephritis (LN) is one of the serious clinical manifestation of Systemic Lupus Erythematosus (SLE). Early detection and treatmentof renal activity may spare patients from renal damage. Conventional biomarkers such as urine sediment, proteinuria, creatinine, antidsDNA antibody and their complement levels are not specific and sensitive enough in detecting the ongoing disease activity in the lupuskidneys and early relapse of nephritis. Renal biopsy is the gold standard in providing information on the histopathology of LN, but isinvasive and it should take a serial of biopsies making it impractical when monitoring LN. Thus, some novel biomarkers are necessary toenhance the diagnostic accuracy and sensitivity of lupus renal disease, prognostic stratification, monitoring of treatment response anddetection of early renal flares as well. Some novel biomarkers have been studied in LN, however, validation on a large scale of patientswith different ethnic backgrounds is still needed.